Barriers and facilitating factors in the prevention of diabetes type 2 and gestational diabetes in vulnerable groups: A scoping review. - Jessica Breuing; Dawid Pieper; Annika Lena Neuhaus; Simone Heß; Lena Lütkemeier; Fabiola Haas; Mark Spiller; Christine Graf (PLoS ONE)
Aims Type 2 diabetes mellitus (T2DM) and gestational diabetes (GDM) are globally on the rise, accompanied by comorbidities and associated health costs. Increased physical activity, healthy nutrition, and weight loss have shown the potential to prevent T2DM/GDM. Despite this, reaching vulnerable groups remains a key challenge. The aim of this scoping review was to identify barriers and facilitating factors in the prevention of T2DM/GDM in vulnerable groups. Methods We conducted a systematic literature search in May 2018, updated in September 2019, in several databases (e.g. PubMed, Embase) to identify barriers and facilitating factors in the prevention of T2DM/GDM in vulnerable groups. Two reviewers independently screened the results. Extracted data was charted, categorized, and summarized. Results We included 125 articles. Ninety-eight studies were extracted, and eight categories of barriers and facilitating factors were formed. The most common categories of barriers were limited knowledge, family/friends, and economic factors, and the most common categories of facilitating factors were family/friends, social support, and knowledge. Conclusion This scoping review identified various barriers and facilitating factors in vulnerable groups. Preventive interventions should consider these barriers and facilitating factors in developing preventive interventions or in adapting existing ones.